Evaluation of a new molecular test for the detection of SARS-CoV-2 Nucleic Acid in salivary samples: A new molecular test for SARS-CoV-2 in salivary samples - Talli, Ilaria; Padoan, Andrea; Moz, Stefania; Navaglia, Filippo; Plebani, Mario; Basso, Daniela (Journal of Medical Biochemistry, 2023)
Background: Molecular testing is considered the gold standard for the detection of SARS-CoV-2. This study aimed to compare the performance of the P742H SARS-CoV-2 Nucleic Acid Multiplex Detection Kit in salivary samples, with respect to the 732HF Novel Coronavirus (2019-nCoV) Nucleic Acid Detection Kit and the TaqPath COVID-19 CE-IVD RT-PCR Kit, used at University-Hospital of Padova, Italy. Methods: One hundred twenty-four salivary samples self-collected by healthcare workers (HCW) during the screening program at University-Hospital of Padova, Italy, from Oct to Nov 2022, were included in the study. RNA extraction was performed by Viral DNA and RNA Extraction Kit (Technogenetics, Lodi, Italy) and amplification by P742H and 732HF (Technogenetics, Lodi, Italy). RNA was extracted using MagNa Pure 96 DNA and Viral NA Small Volume Kit (Roche, Switzerland) for TaqPath analysis (Thermo Fisher Scientific, USA). Results: 94 samples were positive at P742H, while 30 were negative; for 732HF, 96 samples were positive, while 28 were negative, with an overall agreement of 97.5% (Cohen’s κ = 0.930, p < 0.001). TaqPath gave 95 positive samples, and 29 negative results, with an overall agreement of 100% (Cohen’s κ = 1.0, p < 0.001) with respect to P742H, and 97.5% (Cohen’s κ = 0.931, p < 0.001) with respect to 732HF. Comparing cycle threshold (Ct) between the P742H and 732HF, no statistically significant differences were found (p = n.s.). Conclusions: The P742H method proved better performances than 732HF for salivary samples, both presenting the same amplification time. In addition, P742H results were comparable to those obtained through the high-throughput method TaqPath.